Hospitality Employers and Employees’ Perceptions Regarding Covid-19 Support Measures: The Case of the Algarve Region (Portugal) - Nunes Henriques, Cláudia Helena; Carvalho, Fátima Lampreia (Journal of Tourism, Sustainability and Well-being, 2023)
This paper aims at investigating hospitality employers and employees’ perceptions regarding governmental policies and measures implemented during Covid 19 crisis, in the Algarve, one of the most tourist regions of Portugal. The methodological framework is associated with a case study based on a set of 51 interviews to Algarvean hospitality employers and employees. A content analysis of interviews on the effects of the pandemic on hospitality was carried using the software QSR NVivo 12. Covid 19 employment impacts were considered as ‘very high’ and ‘high’ in the Algarvean hospitality. Portuguese governmental intervention was classified as good, but more support should be enhanced, namely associated with four main policy areas such as ‘income-generating support measures’, ‘cost reductions’, ‘legal framework’, and ‘health and safety’.